Exercise intervention in brain injury: a pilot randomized study of Tai Chi Qigong - Blake, Holly; Batson, M. (SAGE, 2009)
Objective: To examine the effects of a brief Tai Chi Chuan Qigong (‘Qigong’) exercise intervention on individuals with traumatic brain injury. Design: A single-centre randomized controlled trial pilot study. Setting: A registered charity day centre in the community. Subjects: Twenty individuals with traumatic brain injury. Intervention: Intervention participants attended a Qigong exercise session for one hour per week over eight weeks. Control participants engaged in non-exercise-based social and leisure activities for the same intervention period. Measures: Outcome was assessed at baseline and post intervention using the General Health Questionnaire-12, the Physical Self-Description Questionnaire and the Social Support for Exercise Habits Scale, to measure perceived mood, self-esteem, flexibility, coordination, physical activity and social support. Results: Groups were comparable at baseline. After the intervention, mood was improved in the exercise group when compared with controls (U ¼ 22.0, P ¼ 0.02). Improvements in self-esteem (Z ¼ 2.397, P ¼ 0.01) and mood (Z ¼ –2.032, P ¼ 0.04) across the study period were also evident in the exercise group only. There were no significant differences in physical functioning between groups. In view of the sample size, these findings are inconclusive. Conclusions: This study provides preliminary evidence that a brief Qigong exercise intervention programme may improve mood and self-esteem for individuals with traumatic brain injury. This needs to be tested in a large-scale randomized trial.